A rabbit model of aneurysmal subarachnoid hemorrhage by ear central artery-suprasellar cistern shunt. (October 2017) - Lu, Jing; Chen, Fuxiang; Cai, Bing; Chen, Fan; Kang, Dezhi
Highlights: A new rabbit model of subarachnoid hemorrhage (SAH) was established. The new SAH model was achieved by ear central artery-suprasellar cistern shunt. Pathophysiological events of early brain injury could be induced in this model. This SAH model was controllable, economical, and easy to operate. Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is a life-threatening hemorrhagic cerebrovascular disease. The concept of early brain injury (EBI), induced by sharply increased intracranial pressure (ICP) and low cerebral perfusion pressure (CPP) with cerebral global ischemia following aneurysm rupture, has been increasingly accepted. However, EBI has not been well studied partly due to lack of an ideal animal model. The purpose of this study was to establish a new aSAH model which can mimic the pathophysiological damage of EBI. Right frontal craniotomy was performed on New Zealand rabbits for placing a PE-50 tube at the suprasella cistern and an ICP probe at the anterior cranial fossa. The central ear artery was punctured and blood was shunted into the suprasellar cistern through the PE-50 tube. ICP, blood pressure, CPP and heart rate peri-aSAH were monitored throughout the experiments. The rabbits were examined for neurological deficits at 24 h post-SAH. Brain coronal sections near the optic chiasma were assessed by HE and Cresyl violet staining. Three minutes after SAH induction, the ICP peaked to 61.7 ± 9.8 mmHg while CPP decreased to nadir 23.5 ± 8.9 mmHg, and both were gradually restored in 15 min. At 24 h post-SAH, significant neurological deficits were found in SAH rabbits as compared to the sham-operated animals. In addition, neuronal degeneration and loss were also detected. Our results indicate that a new rabbit model of aSAH with EBI is successfully established. Moreover, this model is controllable, economical, and no side-injury to the main artery.